Pengaruh Kualitas Layanan Dan Harga Terhadap Kepuasan Pelanggan Mcdonald’s Di Kota Malang - Oktavian A, Muhammad Ilyas; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to evaluate the impact of service quality and price on customer satisfaction. Data was collected through an online questionnaire using the snowball sampling technique. The research sample consisted of 100 students of the management study program, Faculty of Business Economics, University of Islam Malang, Class of 2023. The results show that service quality and price simultaneously have a positive and significant influence on MCD customer satisfaction. In addition, it was found that the quality of service individually affects consumer satisfaction, and price variables also have a significant influence on consumer satisfaction Keywords: Service Quality, Price, Customer Satisfaction